2004
DOI: 10.1109/tsp.2003.822365
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Minimum Distance-Based Precoder for MIMO Spatial Multiplexing Systems

Abstract: We describe a new precoder based on optimization of the minimum Euclidean distance d min between signal points at the receiver side and for use in multiple-input multiple-output (MIMO) spatial multiplexing systems. Assuming that channel state information (CSI) can be made available at the transmitter, the three steps noise whitening, channel diagonalization and dimension reduction, currently used in investigations on MIMO systems, are performed. Thanks to this representation, an optimal d min precoder is deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
139
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 160 publications
(141 citation statements)
references
References 18 publications
(37 reference statements)
2
139
0
Order By: Relevance
“…Hence, the average number of neighbors providing d min is given by N dmin = 1 16 (4 × 2 + 8 × 3 + 4 × 4) = 3. This value is less than the number of the minimum Euclidean distances obtained by the precoder F r1 presented in [7] (N dmin = 1 16 (4×2+4×3+4×4+4×5) = 3.5). However, the distances d min provided by two precoders remain very close.…”
Section: B For Qpsk Modulationmentioning
confidence: 80%
See 4 more Smart Citations
“…Hence, the average number of neighbors providing d min is given by N dmin = 1 16 (4 × 2 + 8 × 3 + 4 × 4) = 3. This value is less than the number of the minimum Euclidean distances obtained by the precoder F r1 presented in [7] (N dmin = 1 16 (4×2+4×3+4×4+4×5) = 3.5). However, the distances d min provided by two precoders remain very close.…”
Section: B For Qpsk Modulationmentioning
confidence: 80%
“…If perfect channel state information (CSI) is considered at both the transmitter and receiver, it was shown that the channel matrix can be diagonalized by using a virtual transformation [7]. The precoder and decoder matrices are then decomposed as…”
Section: System Modelmentioning
confidence: 99%
See 3 more Smart Citations